Eventology and Eventological Method in Emergency Risk Assessment (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Brief information about the eventological method of emergency security evaluated by subject, event, eventology, probability and value. The tariff of subject safety is given. Eventology and importance are given. Elements are defined as radom events as an event.